2022
DOI: 10.3390/jcm11133776
|View full text |Cite
|
Sign up to set email alerts
|

High First Trimester Levels of TSH as an Independent Risk Factor for Gestational Diabetes Mellitus: A Retrospective Cohort Study

Abstract: Although numerous articles have found an association between alterations in thyroid function and the risk of gestational diabetes mellitus (GDM), other studies have failed to demonstrate this association. This may be due to the different cut-off points used to define subclinical hypothyroidism. We aim to clarify the role of thyroid stimulating hormone (TSH) level in GDM within pregnant women with normal free thyroxine (fT4) levels. This retrospective cohort study was performed in 6775 pregnant women. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Several studies evaluated whether the presence of SCH during pregnancy was predictive of development of GDM, as summarized in Table 1. Some studies showed a higher prevalence of SCH among women with GDM when compared with controls [139][140][141][142][143], while other studies [144][145][146][147][148] did not find this association. The varying results of these studies should be interpreted in light of differences in study design, different criteria for diagnosing SCH and GDM during pregnancy and timing of evaluation.…”
Section: Is Sch Associated To An Increased Risk Of Gdm?mentioning
confidence: 93%
See 2 more Smart Citations
“…Several studies evaluated whether the presence of SCH during pregnancy was predictive of development of GDM, as summarized in Table 1. Some studies showed a higher prevalence of SCH among women with GDM when compared with controls [139][140][141][142][143], while other studies [144][145][146][147][148] did not find this association. The varying results of these studies should be interpreted in light of differences in study design, different criteria for diagnosing SCH and GDM during pregnancy and timing of evaluation.…”
Section: Is Sch Associated To An Increased Risk Of Gdm?mentioning
confidence: 93%
“…The majority of data come from retrospective cohort studies [139,[142][143][144][145]149], while other studies [140,147,150,151] were designed as case controls (comparing a group of women with GDM and a control of healthy pregnant women). Some authors used a TSH cutoff lower than nonpregnant normal value [143,147,150], while other used trimester-specific ranges [139,142,144,149,151].…”
Section: Is Sch Associated To An Increased Risk Of Gdm?mentioning
confidence: 99%
See 1 more Smart Citation
“…As a common obstetric metabolic disorder, GDM poses both short- and long-term threats to maternal and child health [ 11 , 24 ]. So far, contradictory conclusions have been drawn to illustrate the causality between thyroid function and the occurrence of GDM [ 11 , 25 , 26 ]. For example, both hypothyroidism (overt/subclinical/isolated) and hyperthyroidism have been reported to be associated with GDM [ 9 , 10 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, both hypothyroidism (overt/subclinical/isolated) and hyperthyroidism have been reported to be associated with GDM [ 9 , 10 , 27 ]. Some studies have indicated adverse relationships of FT4, TSH or both with GDM under euthyroid status [ 4 , 11 , 25 ], whereas other studies indicated contrary relationships [ 7 , 11 , 25 ]. These inconsistencies indicated complex relationships between the thyroid system and glucose homeostasis, which could hardly be explained by a single parameter.…”
Section: Introductionmentioning
confidence: 99%